(untitled) (Al Basirah, 2020)
Almighty Allah revealed the Qur’an as an endorsement of the prophet hood and guidance for people. Moreover, Allah (S.W.T) ordered to think and ponder over the verses of Holy Quran, for example Allah (S.W.T) said in a vers: “This is the Blessed Book that we have revealed to you, (O Muhammad), that people with understanding may reflect over its verses and those with understanding derive a lesson” [38:29], another verse of holy Quran describes “Do they, then, not reflect on the Qur‟an? Or are there locks on their hearts” [47:24] etc. Many scholars worked extensively interpreting the verses of the Holy Quran due to its importance, as emphasized in the above verses, and contributed humongous to the literature of Tafseer and Quranic sciences. Some scholars coined the term „abstruse verses of the Holy Quran‟ an area where it seems that the Quranic verses and Prophetic sayings are conflicting, or the interpretation of our predecessors doesn‟t match with the context of the verse and sometime due to the multiple meanings of a single word also cause a difficulty for a reader. The literature is so vast in this area, thus, it is now considered as a branch of Quranic Sciences: „The abstruse verses of the Holy Quran‟. Scholars from the subcontinent also contributed, and adopted different approaches to elucidate „the abstruse verses of the Holy Quran‟. First book in this field was written by Sheikh Anwar Shah Kashmiri with the title of “Mushkilat ul Quran” (The Problems of the Qur‟an) and this book is considered as a primary source in this field, which indicates its popularity among the scholars of Tafseer & Quranic Sciences in subcontinent. Keeping in mind the importance of this book this article cites the author‟s approach to elucidate so called abstruse verses of Holy Quran.